Total Phenolics, Mineral Elements, Antioxidant and Antibacterial Activities of Some Edible Wild Plants in Turkey - CORUH, IRFAN; ALA GORMEZ, ARZU; ERCISLI, SEZAI; BILEN, SERDAR (Asian Journal of Chemistry, 2010)
Total phenolic content, macro and micro elements (N, P, K, Ca, Mg, Na, Fe, Mn, Zn and Cu), antioxidant and antibacterial activities of leaves of some edible plants (Sinapis arvensis L., Polygonum aviculare L. and Tragopogon aureus Boiss.) grown wild in Eastern Anatolia region of Turkey were studied. The total phenolic content was found between 12.56 μgGAE/mg (T. aureus) and 22.25 μgGAE/mg (S. arvensis). All three species showed high antioxidant activity and among them T. aureus possessed the highest one (88.64 %). There was a low correlation (R = 0.447) between total phenolic content and antioxidant activity in the plant samples. N, P and K values of plants were between 1.98 % (T. aureus) and 3.44 % (S. arvensis); 164 mg/100 g (T. aureus) to 255 mg/100 g (S. arvensis) and 2005 mg/100 g (P. aviculare) to 2710 mg/100 g (T. aureus), respectively. The methanol extracts of the leaves of species showed antibacterial activities against a number of microorganisms searched. However, none of the water extracts of plants showed antibacterial activity on the microorganisms studied.